Transplantation at a glance. - Clatworthy, Menna (At a glance., 2012)
The first basic overview of all aspects of transplantation with a clarity not to be found in more inaccessible textbooks. This brand new title provides a succinct overview of both the scientific and clinical principles of organ transplantation and the types of organ transplant, featuring highly-illustrated information covering core topics in transplantation including:Organ donors. Organ preservation. Assessment of transplant recipients. Indications for transplantation. Immunology of transplantation. Immunosuppression and its complications. Overviews of thoracic and abdominal organ transplantation, in.